1986
DOI: 10.1056/nejm198610023151401
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Atherosclerosis by Cod-Liver Oil in a Hyperlipidemic Swine Model

Abstract: We studied the effect of cod-liver oil on the development and progression of coronary artery disease in swine subjected to coronary balloon abrasion and fed an atherogenic diet for eight months. Sections from serial 3-mm segments of the coronary arteries were analyzed morphometrically in 7 pigs given a cod-liver-oil supplement and 11 control animals not given the supplement. Significantly less disease was seen in the sections from the animals fed cod-liver oil. The mean lesion area per vessel, mean luminal enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0
2

Year Published

1988
1988
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 328 publications
(76 citation statements)
references
References 43 publications
5
69
0
2
Order By: Relevance
“…21 The results of the latter study demonstrated that omega-3 fatty acids not only lowered platelet arachidonic acid and serum thromboxane concentrations, but also had inhibitory effects on both coronary atherosclerosis and intimal hyperplasia after endothelial disruption. It was concluded that the reduction in coronary artery disease was a possible result of altered prostaglandin metabolism.…”
mentioning
confidence: 88%
“…21 The results of the latter study demonstrated that omega-3 fatty acids not only lowered platelet arachidonic acid and serum thromboxane concentrations, but also had inhibitory effects on both coronary atherosclerosis and intimal hyperplasia after endothelial disruption. It was concluded that the reduction in coronary artery disease was a possible result of altered prostaglandin metabolism.…”
mentioning
confidence: 88%
“…The health implication of an increased n-3 VLCPUFA intake is therefore not unequivocal. The diverging results of trials in which animals were fed n-3 VLCPUFA further underscore this uncertainty (Weiner et al, 1986;Davis et al, 1987;Fincham et al, 1991;Barbeau et al, 1997). Accordingly, it is still a controversial issue whether ®sh protects against CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies with hypercholesterolemia Tables 2-4 list the in vivo studies in rabbits [58][59][60][61][62][63][64][65][66][67][68][69], swine [23,28,[70][71][72][73] and monkeys [74][75][76], respectively, on the effects of fish oil on the prevention of atherosclerosis and provides details such as the dietary regimen, duration of study, etc. Except in the Watanabe hereditary hyperlipidemic rabbit and one study in pigs [73], all atherogenic diets are highcholesterol diets, and in case of the swine model [28,[70][71][72], bile acids were also needed to enhance hypercholesterolemia.…”
Section: Fish Oil and The Prevention Of Atherosclerosismentioning
confidence: 99%
“…Except in the Watanabe hereditary hyperlipidemic rabbit and one study in pigs [73], all atherogenic diets are highcholesterol diets, and in case of the swine model [28,[70][71][72], bile acids were also needed to enhance hypercholesterolemia. In small animals (rabbits) usually only the aorta has been used to evaluate the anti-atherogenic effect of fish oil.…”
Section: Fish Oil and The Prevention Of Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation